Testing for break-even effect in the indonesian capital market - Yohanis, Yohanis; Margaretha, Farah; Usman, Bahtiar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to find out whether investors experience  a break-even  effect. The research  method used in this study was the Leal et al. (2017) method to find the break-even  effect. The results show a break-even  effect  in several  years,  2012  and  2015.  This means  that  only in those  two  years  did individual  investors  experience   a  break-even   effect  as  indicated  by  the  Proportion   of  Winners Additionally Purchased (PWAP), which was more significant than the Proportion of Losers Additionally Purchased (PLAP). The limitation of the research  is that there  are still several other methods that can be developed to find the break-even  effect. Bullish and bearish market  conditions are also expected to influence investors' decisions. The research implication for securities companies and capital market authorities is that  it is necessary  to support  individual customers through  education to avoid these two effects. Investors need to be aware of the break-even  effect. Research on individual investors is still minimal. In addition, it uses a sample of secondary  data from individual investor transactions to find the relatively new break-even  effect on the Indonesia Stock Exchange.